PENCARIAN MELODI PADA FILE MIDI - Fajar, Eddo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
Searching MIDI files is generally done by looking at their file names or the metadata/tags inside them. Searching for a certain melody in a MIDI file must be done by looking at the contents on the MIDI file. When searching for a melody in a MIDI file, the user inputs a melody as a query. The system will then search for MIDI files that contain the most similar melodies compared to the query. The queried melody is monophonic while melodies contained in MIDI files are polyphonic. Therefore, melodies in the MIDI files must be converted to monophonic in order to enable comparison. The comparison of two monophonic melodies is done by calculating their dissimilarity factor. The smaller the dissimilarity factor, the more similar the two melodies are. A zero dissimilarity factor means the two melodies are identical. There are two comparison methods used, i.e. bar per bar comparison and note per note comparison. Bar per bar comparison is faster but is very fussy about the position of the melody in the bar. Note per note comparison is more accurate but takes longer to search.